Shells On A Desert Shore Mollusks in the Seri World - Marlett, Cathy Moser, 1952- (Southwest Center series., 2014)
"Shells on a Desert Shore is a fresh, original look at an indigenous culture of North America having a deep and intimate knowledge of the Gulf of California. Cathy Moser Marlett offers a richly illustrated ethnographic work, describing the Seri knowledge of mollusks and their cultural importance"--Del editor.